Probiotics on Commercial Fish Growth: A Meta-Analysis - Ariyanto, Yogy Satria; Anika, Mutia (Jurnal Sumberdaya Hayati, 2024)
Probiotics are widely used in fish diets to improve health and growth, but a detailed analysis of their impact on fish growth performance has been lacking. This study conducted a meta-analysis of 86 relevant articles out of 627 identified, focusing on specific growth rate (SGR) and feed conversion ratio (FCR). The study examined the effects of different variables, including the number of probiotic strains used, the type of water (freshwater, saltwater, or brackish), and the concentration of probiotics. The results indicated that probiotics had a significant positive effect on both SGR and FCR in fish. There was no notable difference in growth performance between diets with single strains versus multiple strains of probiotics. However, freshwater fish showed a better response to probiotics compared to saltwater and brackish water fish. The analysis found that the minimum effective concentration of probiotics for improving SGR was 7 log CFU/g, while 8 log CFU/g was needed to enhance FCR. Overall, this meta-analysis offers valuable insights into optimizing the use of probiotics in aquaculture, demonstrating that specific factors such as water type and probiotic concentration play critical roles in achieving the best growth performance in fish.